How to solve this in matlab?
1 view (last 30 days)
Hi,did someone know how to convert this equation in matlab?i know this is easy since matlab have build in function.but i cant figure it how to do that in matlab,still new in matlab..
Xab = X in pattern a and pattern b
Kab = K in pattern a and pattern b
Paulo Silva on 26 Apr 2011
%pre-allocate the vectors for Xab and Kab
% can't decode this %?Xab.Kab
for a=1:na %a=1...nth value
for b=1:nb %b=1...nth value
Xab(a+b-1)=X; %Xab = X in pattern a and pattern b
Kab(a+b-1)=K; %Kab = K in pattern a and pattern b